2018
DOI: 10.1016/j.bbamem.2018.02.005
|View full text |Cite
|
Sign up to set email alerts
|

Atomistic-level study of the interactions between hIAPP protofibrils and membranes: Influence of pH and lipid composition

Abstract: The pathology of type 2 diabetes mellitus is associated with the aggregation of human islet amyloid polypeptide (hIAPP) and aggregation-mediated membrane disruption. The interactions of hIAPP aggregates with lipid membrane, as well as the effects of pH and lipid composition at the atomic level, remain elusive. Herein, using molecular dynamics simulations, we investigate the interactions of hIAPP protofibrillar oligomers with lipids, and the membrane perturbation that they induce, when they are partially insert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
42
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(46 citation statements)
references
References 71 publications
2
42
0
2
Order By: Relevance
“…Here, a contact was defined if the distance between the heavy atoms of DA/NE molecule and αS tetramer lied within 0.54 nm [65,68]. All the representations of the simulated systems were drawn with the VMD program [69].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Here, a contact was defined if the distance between the heavy atoms of DA/NE molecule and αS tetramer lied within 0.54 nm [65,68]. All the representations of the simulated systems were drawn with the VMD program [69].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies reported that an ion pair can be defined as a salt bridge if the centroids of the side-chain charged-group atoms in the residues (Asp or Glu with Arg, Lys, or His) lie within 4.0 Å of each other, and at least one pair of Asp or Glu side-chain carbonyl oxygen and side-chain nitrogen atom of Arg, Lys, or His is also within this distance [61][62][63]. This criterion has been widely used in many computational studies [64][65][66][67]. Therefore, in this work, a salt bridge was considered to be formed if the minimum distance between the nitrogen atom of side-chain NH 3…”
Section: Simulation Detailsmentioning
confidence: 99%
“…The toxic effects of hIAPP have been linked to perturbation of the cellular membrane by the peptide, specically involving its oligomeric aggregates. 46,47 As such, we also assessed the impact of the C-dots upon the interactions of hIAPP with lipid bilayers (Fig. 4B).…”
Section: Paper Nanoscale Advancesmentioning
confidence: 99%
“…A segunda indicação (ii) de nossos experimentos também está em acordo com resultados da literatura onde se evidenciou que a formação de agregados do IAPP, na presença de lipossomos, acontece na superfície da membrana lipídica [175,180,181]. Primeiramente, há a ligação do monômero do IAPP na superfície da membrana [184], seguido do enovelamento da proteína para uma conformação rica em α hélice [175,180] (ou não [181]). Após, outros monômeros se agregam à estes primeiros e o oligômero formado passa por outra mundança de estrutura secundária rica em folhas β acarretando na formação da fibra amiloide [175,180,181].…”
Section: Resultsunclassified
“…Desta maneira, sugere-se que a membrana lipídica sirva de catalisadora do processo de nucleação do IAPP por oferecer uma superfície de ligação para os monômeros do polipeptídeo, onde o aumento da concentração local desencadearia a fibrilação [180,181]. De fato, simulações computacionais indicaram que o monômero do IAPP se liga à superfície de membranas de DPPG e DPPC:DPPG (7:3) penetrando até 1,62 nm [184].…”
Section: Fluorescência Resolvida No Tempounclassified